2017
DOI: 10.1002/2017gl073857
|View full text |Cite
|
Sign up to set email alerts
|

Rupture processes of the 2016 Kumamoto earthquake sequence: Causes for extreme ground motions

Abstract: We performed joint inversions of strong motion, teleseismic, and geodetic data to investigate the rupture processes of three notable (Mw ≥ 6.0) events of the 2016 Kumamoto earthquake sequence. Multisegment fault models for the three events were constructed based on focal mechanisms, hypocenter distributions of this sequence, and active faults, as well as geodetic features. The results reveal the spatial relationships between the slip distributions of the three events over complex fault planes. In the largest e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 38 publications
7
55
0
Order By: Relevance
“…6b). Thus, the large slip on the Futagawa fault that was observed by the seismic waveform analyses (Asano and Iwata 2016;Kubo et al 2016;Uchide et al 2016;Yagi et al 2016;Kobayashi et al 2017;Hao et al 2017) as well as in the geodetic data (Himematsu and Furuya 2016) would not be produced, even if the D c and S H values are smaller than those used in this study. If D c is much smaller than 0.1 m in case E, the rupture might transfer to the Futagawa fault.…”
Section: Rupture Processes In An Infinite Mediummentioning
confidence: 84%
See 2 more Smart Citations
“…6b). Thus, the large slip on the Futagawa fault that was observed by the seismic waveform analyses (Asano and Iwata 2016;Kubo et al 2016;Uchide et al 2016;Yagi et al 2016;Kobayashi et al 2017;Hao et al 2017) as well as in the geodetic data (Himematsu and Furuya 2016) would not be produced, even if the D c and S H values are smaller than those used in this study. If D c is much smaller than 0.1 m in case E, the rupture might transfer to the Futagawa fault.…”
Section: Rupture Processes In An Infinite Mediummentioning
confidence: 84%
“…1). The largest slip was shown to occur at a portion of the Futagawa fault shallower than 12 km by seismic waveform inversion analyses (Asano and Iwata 2016;Kubo et al 2016;Uchide et al 2016;Yagi et al 2016;Kobayashi et al 2017;Hao et al 2017) as well as in the geodetic data (Himematsu and Furuya 2016). These studies reported the maximum slip amount was 4-6 m. The seismic waveform inversion results suggested that the slip of the main shock occurred on the Hinagu fault first and propagated to the Futagawa fault at a depth of 10-15 km at 2-4 s (Asano and Iwata 2016;Kubo et al 2016;Uchide et al 2016;Hao et al 2017).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…1), and two aftershocks with M JMA magnitude 4.9 and 4.8. The mainshock itself was omitted from the analysis as it has rather complex earthquake source rupture process that was studied in detail in other studies (e.g., Asano and Iwata 2016;Kubo et al 2016;Kobayashi et al 2017). …”
Section: Application To the 2016 Kumamoto Sequencementioning
confidence: 99%
“…The normal faulting was dominant especially in the northeast part of the rupture zone (e.g., Toda et al 2016). Finite source models for the mainshock were inverted from strong motion records (e.g., Asano and Iwata 2016;Kubo et al 2016;Hao et al 2017;Kobayashi et al 2017;Yoshida et al 2017). The inferred models suggest that the M JMA 7.3 event started near the intersection of the Futagawa and Hinagu faults by right-lateral strike-slip movement; then, the rupture propagated to the NE along the Futagawa fault as strike-slip with a normal faulting component.…”
Section: Introductionmentioning
confidence: 99%